"Foreign talent": desire and Singapore's China scholars - Yang, P (2014)
This thesis addresses the “foreign talent” situation in Singapore with an ethnographic account of the lived experiences of immigrant PRC students on scholarships, or “PRC scholars.” For some two decades, the Singapore government has annually recruited middle school students from China in their hundreds, selecting them through tests and interviews, granting them full scholarships at either pre-undergraduate or undergraduate level, and, very often, “bonding” them to work subsequently in Singapore for a number of years. Wooed and appropriated in such a way as prized potential human capital, PRC scholars exemplify the Singapore state’s desire for “foreign talent.” In the first decade of the twenty-first century, as the influx of all manners of “foreign talent” into the small city-state gathered pace, local sentiments and discourses of resentment arose. The local-vs-“foreign talent” problem became a serious strain on a city and people proud of their cosmopolitanism. This thesis analyzes the “foreign talent” situation through the ethnographic “macro-trope” of desire. It argues that “foreign talent” is a site of convergence and divergence, collusion and collision, accommodation and contestation, fulfillment and failure of various individual, sociocultural, and political desires and longings. Through the lens of desire, and its psychoanalytic undertones and insights, this thesis looks ethnographically into the PRC scholars’ “foreign talent” journeys in nuanced ways. Based on ethnographic fieldworks carried out in a Chinese middle school and a Singaporean university, the thesis shows how Chinese students are constituted as specific subjects of desire, and how they subsequently develop certain perceptions, attitudes, and stereotypes about the local “other” as well as about themselves after arriving in Singapore as “foreign talent.” Infused with multifarious desires, the PRC scholars’ experiences are often characterized by angst and dissatisfaction; yet it is also argued that generative subjective transformations take place precisely amidst these dynamics and pragmatics of desiring. Ultimately, this thesis seeks to make possible an ethical re-imagination of the “foreign talent” situation in Singapore from the perspective of desire; to provide an account of the so far little-studied Chinese migrant students in the context of Singapore; and to speak more broadly to the cultural and subjective dimensions of human experiences in the context of educational mobility, identity politics, and globalization.